Pendapatan Pekerja Laki-laki Migran dan Nonmigran pada Sektor Informal di Kelurahan Nendagung Kecamatan PagarAlam Selatan - LUSIANA, LUSIANA WATI; DIDIK, DIDIK SUSETYO; MARYADI, MARYADI MARYADI (Islamic Economics Program, Faculty of Islamic Economics and Business, 2016)
The informal sector is part of the business units that usually found in small scale. The actors of informal sector are not organized, They worked as informal workers in informal sector due to migrations of people from the rural area to the urban area as an effect of inequality of development in rural area. In addition, that migrations happen due to the difficiulty in getting job in rural area. Informal workers, especially street vendors, have positive impacts and negative impacts to urban area. For government, the actors of informal sector sometimes could be the troublemakers, for example: they make the urban layout not beautiful as usual. The actors of informal sector tends to do their businesses everywhere without thinking whether their business locations are right or wrong. Their businesses are the cause of traffic jam , uncleanliness and untidiness in rural area. That problems make the reseacher has an interest to research about these informal workers, especially male migrant workers and male nonmigrant workers.Researcher uses census sampling technique for this research. Researchere use this technique due to the population size of this research is small and the population of this research is easy to reach. The sample size is 101 people of informal sector workers that lived in Nendagung Village, Pagar Alam Selatan Subdistrict.The analysis technique that used in this thesis is multiple linear regression. The purpose of that technique are to know whether the simultantly and partially effect of education level, working experience, working hours, side job and dependants of households to income of male migrant workers and income of male nonmigrant workers that lived in Nendagung Village, Pagar Alam Selatan Subdistrict, are significant or not. The findings of this research are educational level affect the income of male nonmigrant workers significantly whereas educational level and working experience affect the income of male migrant workers significantly.Keywords : Income, Migrant Nonmigrant, Informal